Content -based trademark retrieval using zernike moments and colour-spatial technigues - Wan Nurul Jawahir, Wan Yussof (Fakulti Sains dan Teknologi, 2011)
The volume of registered trademarks are increasing tremendously in recent years. This has led to the urgent need for efficient retrieval of registered trademarks to protect them from infringement, misuse or imitation. By using content-based image retrieval technique, an efficient and automatic trademark retrieval system is developed. The use of content-based trademark image retrieval technique is proposed because difficulty in formulating meaningful queries by using keyword-based system which is almost impossible in describing visual perceptual similarity of trademark images.